PENGARUH PEMBERIAN TAWAS DENGAN DOSIS BERTINGKAT DALAM PAKAN SELAMA 30 HARI TERHADAP GAMBARAN HISTOPATOLOGI HEPAR TIKUS WISTAR - Putri Rizki Ananda; Akhmad Ismail (Faculty of Medicine, Universitas Diponegoro, Semarang, Indonesia, 2016)
Background : Alum was in the form of white crystals and gelatin used in the water purification process, but there was still many misuses as a food coloring and food preservatives. Alum has the harmful side effects to the body, especially hepar as an organ that plays a role in the metabolism and detoxification.Aim : To determined differences in hepar histopathology wistar rats of alum exposure with graded dosages for 30 days.Metods : This was an experimental laboratoric research study design with a post test only control group design. There were 20 wistar rats, which have met the inclusion and exclusion criteria and adapted for 7 days. Then, wistar rats devided by simple random sampling into 4 groups. The control group (C) who were given only standard food and bevarages, group P1 given alum in feed 2400mg/kg body weight/day, group P2 given alum in feed 1600mg/kg body weight/day, and group P3 given alum in feed 800mg/kg body weight/day. After 30 days, histopathological examinated of hepar form degeneration and inflammation. Data described on the tabel, picture, and statistic analyze.Result : Mean of inflammation and degeneration hepar cell was the biggest in the group of P1. In inflammation, there was significant difference (p<0,05) in the group of C-P1, C-P2, C-P3, P1-P3, and P2-P3, although P1-P2 was not significant difference. In degeneration of hepar cell, there was significant difference (p<0,05) in the group of C-P1, C-P2, C-P3, P1-P3, and P2-P3, although P1-P2 was not significant difference.Conclusion : Giving alum in feed with graded dosage for 30 days cause change of wistar rats hepar histopathology.